STRATEGI MENINGKATKAN PENGENALAN MEMBACA ANAK USIA DINI (AUD) DENGAN METODE ANAK HEBAT (AHE) - Ubaidillah; Listianah, Listianah (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
This research is motivated by the background that there are still Early Childhood (AUD) who are difficult to recognize letters so that they have low reading skills, this worries some parents who want the best education for their children, Regarding this the AHE reading method provides solutions to several parental problems for the educational needs of their children, providing a reading introduction strategy using the Great Child (AHE) method. AHE is one of the many reading methods that provide some surefire step strategies to guide children in reading learning activities. In the AHE method, there are 6 strategies for the learning process steps. The 6 steps are brain gymnastics, remidi, reading modules, enrichment, writing and the last is games